Psychological Symptom Progression in School-Aged Children After COVID-19 Home Confinement: A Longitudinal Study - Xie, Xinyan; Liu, Qi; Zhu, Kaiheng; Jiang, Qi; Feng, Yanan; Xiao, Pei; Wu, Xiaoqian; Song, Ranran (Frontiers in Psychiatry, 2022)
Background: The long-term mental health effects of coronavirus disease 2019 (COVID-19) in children are rarely reported. We aimed to investigate the progression of depressive and anxiety symptoms among a cohort of children in the initial epicenter of COVID-19 in China. Methods: Two waves of surveys were conducted in the same two primary schools in Wuhan and Huangshi, Hubei province: Wave 1 from 28 February to 5 March, 2020 (children had been confined to home for 30–40 days) and Wave 2 from 27 November to 9 December, 2020 (schools had reopened for nearly three months). Depressive and anxiety symptoms were estimated using the Children’s Depression Inventory – Short Form (CDI-S) and the Screen for Child Anxiety Related Emotional Disorders (SCARED), respectively. ΔCDI-S and ΔSCARED scores between Wave 2 and Wave 1 were calculated and further categorized into tertiles. Multivariable linear regression and multinomial logistic regression models were then applied. Results: A total of 1224 children completed both surveys. The prevalence of mental health outcomes at Wave 2 increased significantly compared to Wave 1: specifically, depressive symptoms (age-standardized prevalence rates: 37.5% vs. 21.8%) and anxiety symptoms (age-standardized prevalence rates: 24.0% vs. 19.6%). Higher ΔSCARED scores were observed in females and children in Wuhan, and children with experience of neglect had higher ΔCDI-S (β = 1.12; 95% CI = 0.67–1.58) and ΔSCARED (β = 6.46; 95% CI = 4.73–8.19) scores compared with those without experience of neglect. When the Δ scores were further categorized into tertiles, similar results were found. Conclusions: The prevalence of depressive and anxiety symptoms after schools resumed was increased compared with that during the home quarantine period, even though the COVID-19 pandemic was under control. Females and children in Wuhan, and also children with experience of neglect, were at increased risk of mental health disorders.